Breastfeeding exposure is associated with better knowledge of and attitudes toward BF in Kuwaiti women - Alkazemi, Dalal Usamah (BMJ Nutr Prev Health, 2019)
OBJECTIVES: Breastfeeding (BF) has many benefits for both infants and mothers. However, despite evidence in support of BF, its prevalence has remained low in Kuwait. The purpose of this study was to (1) assess and describe BF attitudes and knowledge among women at a college campus; (2) evaluate BF exposures and sociodemographic factors associated with attitudes toward BF; (3) determine the association between BF knowledge and attitudes. MATERIALS AND METHODS: This survey was a cross-sectional descriptive study conducted from February to April 2016. A convenience sample of 330 women (students, faculty and staff) from the College of Life Sciences (CLS) at Kuwait University participated in the survey. RESULTS: Most of the participants respected women who breast fed (81.8%). Some participants believed that BF a baby is painful (43.3%), makes the breasts sag (35.8%), and restricts the mothers’ freedom (51.5%). Additionally, 47.6% of the participants reported that they would feel embarrassed if they saw a woman BF her baby. Acceptability of BF in public was low and most participants preferred BF only around friends and family (52.4%). A statistically significant positive association was observed between BF knowledge and attitudes (R(2)=6.5%, p<0.001); however, the relationship was not independent and was also associated with nationality and having been breast fed as a baby (R(2)=10.3%, p=0.021). CONCLUSION: BF knowledge is important to encourage positive BF attitudes, and both are enforced with family values and practice across generations.